2016
DOI: 10.7739/jkafn.2016.23.4.411
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nursing Students’ Anxiety during Simulation Training on Personal Satisfaction of Simulation, Self-efficacy, Clinical Competence

Abstract: The purposes of this study were to identify nursing students' levels of anxiety in simulation based nursing education and to understand the relationship of anxiety and personal satisfaction of simulation, self-efficacy, and clinical competence during simulation. Methods: This study was a descriptive study with 84 senior nursing students at a private university in South Korea. Level of anxiety was measured with STAI (the State-Trait Anxiety Inventory) prior to the stimulation practice. After the debriefing, sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Although the number of participants in these two years was not the same, the difference may be because coping skills and clinical performance improve as the student progresses in the course, and their simulation experience increases. The high level of anxiety among junior students who had no clinical experience, and the positive correlation between clinical performance and anxiety during simulation are consistent with previous studies [28,29]. Therefore, it is necessary to provide basic information about a simulation scenario, even if the scenario is not disclosed for the purpose of learning.…”
Section: Discussionsupporting
confidence: 86%
“…Although the number of participants in these two years was not the same, the difference may be because coping skills and clinical performance improve as the student progresses in the course, and their simulation experience increases. The high level of anxiety among junior students who had no clinical experience, and the positive correlation between clinical performance and anxiety during simulation are consistent with previous studies [28,29]. Therefore, it is necessary to provide basic information about a simulation scenario, even if the scenario is not disclosed for the purpose of learning.…”
Section: Discussionsupporting
confidence: 86%
“…Students' anxiety during simulation reduces self-efficacy and clinical performance [21]. Therefore, to promote team-efficacy, students were introduced to SP before the start of the simulation so that it allows for a high-fidelity simulator and for students to check the practice environment in advance to reduce the burden and anxiety of students.…”
Section: ) Simulation Runningmentioning
confidence: 99%
“…The teaching and learning method, using simulations, allows learners to actively participate in learning in order to raise their nursing performance ability based on clinical field cases [ 6 , 7 , 8 ]. Further, simulation practicum contributes to the improvement of nursing students’ problem-solving ability, clinical performance, and knowledge, as well as some degree of learning satisfaction [ 6 , 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The teaching and learning method, using simulations, allows learners to actively participate in learning in order to raise their nursing performance ability based on clinical field cases [ 6 , 7 , 8 ]. Further, simulation practicum contributes to the improvement of nursing students’ problem-solving ability, clinical performance, and knowledge, as well as some degree of learning satisfaction [ 6 , 7 , 9 ]. However, the teaching and learning method, using simulations, is known to increase stress because of the tension and anxiety of actual situations, and it is reported that it causes fears of making mistakes and decreases the self-efficacy and learning satisfaction of nursing students [ 5 , 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation